2021
DOI: 10.3390/jcm10173763
|View full text |Cite
|
Sign up to set email alerts
|

Association between Tooth Loss and Alzheimer’s Disease in a Nested Case–Control Study Based on a National Health Screening Cohort

Abstract: Background: Reports on the possible risks for Alzheimer’s disease (AD) have included tooth loss as a potential risk factor. However, there are few studies addressing the association between tooth loss and AD in a large sample of participants. Accordingly, the objective of the current study was to explore the association of tooth loss with the development of AD in Korean adults. Methods: This nested case–control study, which is an analysis utilizing the data of the Korean National Health Insurance Service Healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(31 citation statements)
references
References 33 publications
0
31
0
Order By: Relevance
“… 5 , 6 , 7 Among the many risk factors for dementia and cognitive decline, oral health measures (e.g., periodontitis, tooth loss) have only started to be recently explored. 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 5 , 6 , 7 Among the many risk factors for dementia and cognitive decline, oral health measures (e.g., periodontitis, tooth loss) have only started to be recently explored. 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 …”
Section: Introductionmentioning
confidence: 99%
“…19 The available evidence on periodontal health and cognitive deterioration is insufficient and subject to limitations. 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 Most individual studies lack comprehensive exposure and outcome assessments and have a shorter duration. Also, in the past two years, several studies have been published 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 which warrant synthesis and evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…While it is not clear whether poor oral health predicts dementia, substantial data suggests that oral health declines as cognitive impairment and dementia progresses [ 7 , 12 , 14 , 15 , 16 ]. Furthermore, it has been demonstrated that masticatory exercise improves cognitive function in older adults [ 17 ] and thus the link between cognitive decline and masticatory dysfunction is now clear [ 8 , 18 , 19 , 20 , 21 , 22 ]. As loss of masticatory activity [ 8 , 11 , 12 , 13 , 18 , 19 , 20 , 21 , 22 ] and sedentary life style [ 23 , 24 ] are risk factors for age-related cognitive decline, there is a need to focus attention on those sub-populations that experience greater oral health deterioration or impairment of the stomatognathic system, and those having living sedentary lives.…”
Section: Introductionmentioning
confidence: 99%
“…However, most previous studies have focused on all-cause or cardiovascular and/or cancer-related mortality and have not considered various causes of mortality that are possibly affected by missing teeth. In addition, although many previous studies have examined the effects of a considerable number of missing teeth (<20 teeth remaining or edentation) on mortality, (1,4,5,(10)(11)(12) only a few prior studies have suggested the effects of a small number of missing teeth on morbidities (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, having <20 teeth and masticatory dysfunction were connected with a greater risk of cognitive deficits in a meta-analysis (OR = 2.24, 95% 95% CI = 1.73–2.90) ( 6 ). Another meta-analysis demonstrated a 1.48 times greater risk of cognitive impairment (95% CI = 1.18–1.87) in individuals with missing teeth with a dose-response association according to the number of missing teeth from 4 to 32 teeth or 0 to 32 teeth ( 7 , 8 ). A prospective cohort study estimated a 1.85 times greater risk of dementia in Japanese elderly individuals with few teeth (95% CI = 1.04–3.31) ( 9 ).…”
Section: Introductionmentioning
confidence: 99%